High Performance Organization: A Case Study of the Logistics Industry in Thailand - Suangsub, Pennapat; Chemsripong, Sujinda; Srisermpoke, Krirtkiat (Journal of Community Development Research (Humanities and Social Sciences); Vol 15 No 1 (2022): January - March 2022DO - 10.14456/jcdr-hs.2022.9, 2022)
This research aimed to analyze the key factors affecting High Performance Organizations (HPO) using a case study of the logistics industry in Thailand by studying the relationship between High Performance Work Systems (HPWS) and the High Performing Organization (HPO) of the logistics industry in Thailand, using a mixed methods research model with a combination of both quantitative and qualitative methods of research in both data collection and analysis. Quantitative research was used to analyze with the structural equation analysis method. The questionnaire was used as a research instrument, using a 5-level Likert assessment scale. The sample group was 260 companies (Third Party Logistics Service Provider: 3PLs) which are leading and reputable companies in the logistics industry of Thailand, developed by the Department of Business Development and had received ISO 9001 certification. The qualitative research was conducted by using an in-depth interview method with the executive members of the logistics service provider type 3PLs of four companies selected for the company’s readiness to cooperate and provide information in the interview. Data and statistics analysis using descriptive statistics included percentage, average, and standard deviation. Statistical software (SPSS) was used for descriptive statistics and analysis by inferential statistics used statistical software (AMOS); two solutions were to analyze the survey by using Exploratory Factor Analysis (EFA) and Path Analysis (PA). From the results of the research, it can be concluded that the High Performance Work System (HPWS) is significantly and positively related to the achievement of a High Performance Organization (HPO) of the logistics industry in Thailand, consisting of three sub-factors: 1) social system factors as people; 2) technical system factors as work process; and 3) supporting system factors using information technology. There were direct and indirect influences on the high performance organization, and it was also found that the social system subfactors (people) had the greatest influence on management systems in the high performance organization of the logistics industry in Thailand. The overall component weight of 0.738 was a result of all indirect influences, followed by the technical system factors as work process with an element weight value of 0.410 and the supporting system factors using information technology to influence high performance organizations which influenced in the opposite direction with the element weight value of -0.361. This study contributes to the enrichment of the literature on the HPWS and HPO by proposing a model that was empirically tested on the validity and reliability in predicting a High Performance Organization (HPO). Keywords: High Performance Organization (HPO), High Performance Work Systems (HPWS), Logistics Industry